Treated knitted fabric for hip protective pads for elderly women. Part II. Performance relevant to thermal comfort. Issue 23 (December 2019) - Wardiningsih, Wiah; Troynikov, Olga
This paper describes Part II of a study of hip protective pads made from spacer fabric treated with shear thickening fluid (STF). Hip fractures are a substantial contributor to morbidity and mortality in the elderly, and incidence is rising worldwide. Hip protective pads reduce fractures, but wearing adherence is poor. Pads made from breathable and comfortable fabrics can increase adherence and prevent more hip fractures. In this research, warp-knitted spacer fabrics were treated with STF using one of two methods. Treatment I involved STF and room temperature vulcanizing (RTV) silicone, while treatment II consisted of STF and a mixture of isopropyl alcohol and tetraisopropyl titanate. In Part I, STF-treated knitted spacer fabric was shown to have significantly greater force attenuation capacity than untreated fabric and comparable to force attenuation capacity of closed cell foam. In Part II, the effects on performance relevant to the thermal comfort of the wearer of each treatment method, the amount of STF used, and layering were assessed using a sweating guarded hot plate, and comparisons made between treated fabrics and with closed cell foam. Treatments I and II produced pads with significantly different permeability index and mass compared to closed cell foam. Treatment II produced pads with high force attenuation capacity, suitable permeability indexes, and low mass – preferred characteristics in hip protective pads. The study concluded that knitted spacer fabrics treated with STF, isopropyl alcohol, and tetraisopropyl titanate are potentially useful materials for hip protective pads.